2017
DOI: 10.1021/acs.langmuir.6b04119
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Isosteric Heat of Adsorption by Quenched Solid Density Functional Theory

Abstract: The heat of adsorption is one of the most important parameters characterizing energetic heterogeneity of the adsorbent surface. Heats of adsorption are either determined directly by calorimetry or calculated from adsorption isotherms measured at different temperatures using the thermodynamic Clausius-Clapeyron equation. Here, we present a method for calculating the isosteric heat of adsorption that requires as input only a single adsorption isotherm measured at one temperature. The proposed method is implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 55 publications
1
50
0
Order By: Relevance
“…The figure presents curves with very similar behavior: initially, they decay from approximately a value of −48 kJ•mol −1 to a value of −27 kJ•mol −1 where later they reach a plateau. This zone is very characteristic for solids of this type and is typical of thermal behavior of the isostere on a heterogeneous surface [22,31,33]. In this area the values evaluated by the three methods are very similar, however, with the low standard deviation of the adsorption calorimetry (A-Cal), it is observed that the indirect methods always underestimated the heat.…”
Section: Isosteric Heat: Comparison Of Csk C-c and Adsorption Calorimentioning
confidence: 83%
See 4 more Smart Citations
“…The figure presents curves with very similar behavior: initially, they decay from approximately a value of −48 kJ•mol −1 to a value of −27 kJ•mol −1 where later they reach a plateau. This zone is very characteristic for solids of this type and is typical of thermal behavior of the isostere on a heterogeneous surface [22,31,33]. In this area the values evaluated by the three methods are very similar, however, with the low standard deviation of the adsorption calorimetry (A-Cal), it is observed that the indirect methods always underestimated the heat.…”
Section: Isosteric Heat: Comparison Of Csk C-c and Adsorption Calorimentioning
confidence: 83%
“…In this area the values evaluated by the three methods are very similar, however, with the low standard deviation of the adsorption calorimetry (A-Cal), it is observed that the indirect methods always underestimated the heat. In the area where the plateau is reached, which ranges from 1 to 3.5 mmol•g −1 , corresponds to isosteric heats that occur on homogeneous surfaces [22,31]. Subsequently, there is an increase in the enthalpic value of isosteric heat of −32 to −48 kJ•mol −1 , which is probably due to interactions of the N2 molecule within the porous structure of MOF-199.…”
Section: Isosteric Heat: Comparison Of Csk C-c and Adsorption Calorimentioning
confidence: 97%
See 3 more Smart Citations